THE ROLE OF ADDING HUMIC ACID AND SEAWEED EXTRACTS BY SPRAYING ON SOME SOIL CHARACTERISTICS AND THE GROWTH AND YIELD OF BARLEY - Entsar Abdul khaleq turkey; Douaa hafedh mousa (Web of Journals Publishing, 2025)
The experiment was conducted in the winter of 2024-2025 on farmland under the Ministry of Agricultural Guidance and Training (Al-Saddah, Al-Mahnawiyah). The aim was to investigate the effects of three concentrations (0, 100, and 150 mg/L-1) of humic acid spray on plants, as well as three concentrations (0, 1, and 2) of seaweed spray on plants. A randomized completely block design (RCBD) was used, and means were compared using the least significant difference (LSD) test at a 5% significance level. The results showed that after spraying humic acid, some physical and chemical properties of the soil, such as apparent density, water content, soil electrical conductivity EC, soil reactivity pH, and some indicators of plant nutritional growth, such as plant height and number of ears, were significantly improved. The humic acid spraying treatment (2 L/dun am) achieved the highest mean values for the above soil properties and crop growth indicators. The interaction treatment (humic acid spraying treatment (2 L/dun am) and seaweed extract 150 mg/L) also achieved the highest mean values.
Keywords: Humic acid, seaweed extracts, barley.